PENGARUH RETURN ON EQUITY (ROE), RETURN ON ASSET (ROA) DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER - Al Adiah; Hanifah; Sri Intan Purnama (The Asia Pacific Journal Of Management Studies, 2023)
This study was conducted to determine the effect of Return on Equity, Return on Assets, and Net Profit Margin on Stock Returns in Primary Consumer Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The method used in this study is a quantitative method and uses secondary data types. The sample used is 29 primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The amount of data used is 145 data selected by using purposive sampling. The data analysis used is multiple linear regression analysis processed using SPSS Version 25. The results of the simultaneous F test are Return on Equity, Return on Assets, and Net Profit Margin on Stock Return. With partial t test Return on Assets (ROA) has an effect on Stock Return. And Net Profit Margin (NPM) has an effect on Stock Return. Meanwhile, Return on Equity (ROE) has no effect on Stock Return.